Acetabular Osteoarticular Allograft After Ewing Sarcoma Resection: A 15-Year Follow-up. Issue 4 (October 2016) - Riff, Andrew J.; Gross, Christopher E.; Foucher, Kharma C.; Kuo, Ken N.; Gitelis, Steven
Abstract : Case: A 4-year-old girl with Ewing sarcoma of the periacetabular region had been treated with neoadjuvant chemotherapy followed by resection and osteoarticular allograft reconstruction with an adult hemipelvis. At 15 years postoperatively, she remained disease-free with remarkable functionality. She had minimal groin pain and could walk an unlimited distance. Radiographs demonstrated union at the anastomotic junctions. The allograft, which had been considerably oversized 15 years ago, was now identical in size to the contralateral ilium. Conclusion: Osteoarticular allograft remains one of the best reconstructive options following hemipelvectomy in the pediatric population because of its potential durability and its capacity to restore pelvic stability and preserve functionality.